TMC (Thrissur Medical College) modified Robson criteria for caesarean sections - Jacob, K. J.; Jayaprakash, Megha; K. P., Hibina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The Robson system is the most widely accepted classification system available for analysing characteristics of delivering women worldwide. Several authors have tried modifications in the existing system. The objective of this study was to modify the existing system with relevance to caesarean section rates in various obstetric population and to identify major factors contributing to it. Methods: This study was performed in Government Medical College, Thrissur from January 2017 to June 2017. All women delivered during this period were classified according to the modified system consisting of 8 groups using their maternal characteristics and obstetric history. Each major group were sub classified into 3: women who went into spontaneous labour/ induced labour/ CS done before labour. For each group, we calculated the contribution to overall CS and Primary CS separately. Women with Previous CS were analyzed as a separate group. This classification was intended to directly estimate primary as well as repeat CS rates and indirectly the VBAC rates. Results: Out of total 1337 women delivered, 413 underwent CS (30.8%). The contribution made by previous CS group to overall CS was 61.5%, and the repeat section rate was 91.3%. The primary CS rate was 15% and the maximum contribution was made by term induced primigravida followed by Primigravida with Breech presentation. VBAC rate was 8.6%. Conclusions: Our modified Robson system can be effectively utilized in analysing delivering women and provide valuable information regarding the delivery characteristics with particular relevance to Caesarean sections.